Effect of Hair Particle Filler on the Characteristics of Green Composite Based on Bacterial Cellulose - Umi Lailatul Jamilah; Endhah Purwandari; Sujito Sujito (Green Engineering Society, 2026)
The growing demand for sustainable materials and effective waste management has encouraged the development of environmentally friendly composites. Green composites are a promising alternative to conventional materials for environmental preservation. In this study, bacterial cellulose derived from nata de coco was used as a matrix, while haircut waste particles served as a filler. Composites were fabricated via compression molding at 170 °C with filler contents of 0, 15, 25, 35, and 45 wt.%. The synthesized materials were characterized through tensile testing, scanning electron microscopy (SEM), and Fourier transform infrared (FTIR) spectroscopy. Increasing hair-particle content increased the elastic modulus from 44.11 ± 3.02 MPa (A1) to 130.46 ± 4.94 MPa (A2), indicating enhanced stiffness of the composite; however, further increases in filler content slightly reduced the modulus due to possible void formation and weaker interfacial adhesion. In contrast, the tensile strength decreased progressively from 11.54 ± 0.56 MPa (A1) to 5.16 ± 0.52 MPa (A5) with increasing filler content. SEM observations revealed the formation of voids and weaker matrix–filler interactions at higher filler contents, which contributed to the reduction in tensile strength. FTIR spectra showed the presence of O–H, C–H, and C=O functional groups, suggesting possible interactions between bacterial cellulose and hair particles. Overall, a filler content of 15 wt.% provides the best balance between stiffness and structural integrity, demonstrating the potential of hair waste as a sustainable reinforcement in bacterial cellulose-based green composites.